Parametric influence on the synthesis and characterization of Covalent Organic Framework-1 (COF-1) / Muhammad Falaq Muhammad Faisal - Muhammad Faisal, Muhammad Falaq (2015)
Covalent Organic Framework (COF) which is a white crystalline nanoporous material, has a very high specific surface area, rigid structure and low in density. COF is made up of light elements which are covalently bonded together and has been studied extensively as a material for gas storage. However, elementary studies on the parametric influence on the characteristics of COFs have not been previously studied. Thus, the objective of this present study is to evaluate COF-1 with modifications to its selected synthesis parameters. The porous character of COF-1 was further studied as a possible catalyst support for Palladium metal (Pd/COF-1). Six samples of COF-1 were synthesized using condensation reaction of 1,4-benzene diboronic acid (BDBA) with modification to its initial mass of BDBA used, the heating condition and the cooling condition. For BDBA, three masses are selected (12.5 mg, 50 mg, 100 mg) with two heating conditions (constant and ramping) and two cooling conditions (open air and moisture free). For constant heating the temperature was set at 100°C while three temperature intervals of 80°C, 95°C and 1000e were selected for ramp heating. The heating time was three days. For open air cooling, sample was cooled at ambient temperature while a desiccator was used for moisture free cooling. Pd/COF-1 was synthesized using dry impregnation method with Palladium (II) nitrate dehydrate, Pd(N0₃)₂.H₂0 as precursor and 0.2 wt% loading. Porosity characteristics were evaluated for all samples with further characterizations using XRD, FESEM and FTIR analyses. It was found that the best COF-1 synthesized in term of the highest BET surface area obtained is COF-1 (S3) with 107.9 m²/g which is a mesoporous structure based on its isotherm profile. Its parametric conditions are 100 mg of BDBA used, constant heating and open air cooling. This sample has also the highest yield of 81.2 % with 34% mesoporosity, total pore volume of 0.2981 cm³/g and average pore diameter of 11.05 nm. The change in the analyses confirms the effect of Palladium metal on COF-1, in which the Pd/COF-1 synthesized shows potential application as a catalyst.